Learning to Write and Writing to Write: Composition Instruction from Habit Formation to Cognition - Kebieche, Amin (Journal of Human Sciences, 2020)
Over the last fifty years or thereabouts, there has been an upsurge in SL/FL rhetoric studies that have given rise to a panoply of theories and approaches that have contributed and still contribute to a better teaching and learning of writing. This paper aims at offering a an account of the ingenious methods to teach writing. In actual fact, such theoretical frameworks draw heavily upon the various learning processes which were put forward all along the twentieth century, viz. behaviorism (habit formation) and cognitivism (cognitive science). What truly characterized the evolution of such spectrum is the shift from focusing on the final product to focusing on the composing processes. Indeed, the shift was from a focus on syntactic maturity and grammatical accuracy at the sentence level, to a focus on the different rhetorical functions at the discourse level.